An ad hoc three dimensionally printed tool facilitates intraesophageal suturing in experimental surgery - Steinemann, Daniel; Müller, Philip C.; Apitz, Martin; Nickel, Felix; Kenngott, Hannes Götz; Müller, Beat P.; Linke, Georg R. (Journal of surgical research, 2017)
Background: Three-dimensional printing (3DP) has become popular for development of anatomic models, preoperative planning, and production of tailored implants. A novel laparoscopic, transgastric procedure for distal esophageal mucosectomy was developed. During this procedure, a space holder had to be introduced into the distal esophagus for exposure during suturing. The production process and evaluation of a 3DP space holder are described herein. Materials and methods: Computer-aided design software was used to develop models printed from polylactic acid. The prototype was adapted after testing in a cadaveric model. Subsequently, the device was evaluated in a nonsurvival porcine model. A mucosal purse-string suture was placed as orally as possible in the esophagus, in the intervention group with and in the control group without use of the tool (n = 8 each). The distance of the stitches from the Z-line was measured. The variability of stitches indicated the suture quality Results: The median maximum distance from the Z-line to purse-string suture was larger in the intervention group (5.0 [3.3-6.4] versus 2.4 [2.0-4.1] cm; P = 0.013). The time taken to place the sutures was shorter in the control group (P < 0.001). Stitch variance tended to be greater in the intervention group (2.3 [0.9-2.5] versus 0.7 [0.2-0.4] cm; P = 0.051). The time required for design and production of a tailored tool was less than 24 h. Conclusions: 3DP in experimental surgery enables rapid production, permits repeated adaptation until a tailored tool is obtained, and ensures independence from industrial partners. With the aid of the space holder more orally located esophageal lesions came within reach.
Gesehen am 14.04.2020